Application development of VCare circle for Utarian - Tan, Zhi Yuan (2023)
For this project, it is done for the purpose of helping UTAR university students in UTAR Kampar. Asking for help is a good method to solve the issues faced by anyone as it is time efficient and effective, while also promoting one’s growth to adjust in different environments easily. However, not all people are capable of doing so as when they face difficulty, they are in a state of confusion on who to ask and how to approach someone for help. For example, when a student is facing difficulty in the university, there is no people around for them to ask for help as they don’t know who can help them to solve this problem. Problems such as unable to locate particular buildings are mostly faced by new students when they are trying to get familiar with the new university life and environment. Thus, a mobile application called VCare Circle as an online assist platform is developed to allow people to ask for help when they need it. For example, when a university student does not know the direction of heritage hall of UTAR, he or she can utilize the project mobile application by login through the registered account to be automatically assigned to a random registered volunteer or helper. The project mobile application allows him or her to get contact with the anonymous helper in order to get advice to determine the exact location of the hall. For this project, the fields of study involved application development, mobile application, and data analysis. In the development of the project, the system methodology used to develop this project is the Rapid Application Development (RAD) methodology to ensure the complexity of framework design and smoothness in the development process. The techniques and equipment involved are the use of Android Studio, Visual Studio Code, Firebase, a mobile device and laptop, Dart programming language, and Google Flutter. Self-manual stimulation testing is done to conduct testing on the project mobile application based on its required functional and non-functional requirements. In conclusion, this system can help students to get familiar with the surroundings of UTAR Kampar, while being able to ask for help anytime and anywhere when they are in need.